2019
DOI: 10.1007/s00384-019-03488-8
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors of short-term survival in the aged in elective colon cancer surgery: a population-based study

Abstract: Purpose Patients aged > 80 years represent an increasing proportion of colon cancer diagnoses. Selecting patients for elective surgery is challenging because of possibly compromised health status and functional decline. The aim of this retrospective, population-based study was to identify risk factors and health measures that predict short-term mortality after elective colon cancer surgery in the aged. Methods All patients > 80 years operated electively for stages I-III colon cancer from 2005 to 2016 in four F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
19
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(26 citation statements)
references
References 37 publications
6
19
1
Order By: Relevance
“…In conclusion, this study extends our earlier findings [8] and suggests that aged colon cancer patients who are physically and functionally fit to survive surgery can achieve acceptable long‐term outcomes and survival with radical surgical treatment and additional chemotherapy. Further prospective studies are required to identify patients who are at risk of complications and able to recover from them as well as the effects of colon cancer surgery on the quality of life in long‐term follow‐up.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…In conclusion, this study extends our earlier findings [8] and suggests that aged colon cancer patients who are physically and functionally fit to survive surgery can achieve acceptable long‐term outcomes and survival with radical surgical treatment and additional chemotherapy. Further prospective studies are required to identify patients who are at risk of complications and able to recover from them as well as the effects of colon cancer surgery on the quality of life in long‐term follow‐up.…”
Section: Discussionsupporting
confidence: 89%
“…However, those who survived the first three postoperative months had survival rates comparable to those with no or mild complications. Thus, preventing complications through preoperative health evaluation is essential, especially for high‐risk patients [8].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although Niemelainen et al [ 17 ] previously reported that comorbid diabetes increases the likelihood of postoperative complications in older patients with stage I-III colon cancer undergoing open or laparoscopic surgery [ 17 ], the present analysis of the NIS (2005-2010) unexpectedly revealed that comorbid diabetes was significantly associated with lower risks of not only postoperative complications but also in-hospital mortality in stage I/II colon cancer patients undergoing open colectomy. Patients with uncomplicated diabetes had significantly lower percentages of in-hospital mortality and postoperative complications than those without diabetes, but patients with complicated diabetes had a significantly higher percentage of postoperative complications than those without diabetes, suggesting that the putative protective role of comorbid diabetes may be mainly contributed by uncomplicated diabetes.…”
Section: Discussioncontrasting
confidence: 67%
“…However, most studies that investigated the effect of comorbid diabetes on short-term surgical outcomes in colorectal cancer did not distinguish colon cancer from rectal cancer [ 13 16 ]. Notably, a population-based study specifically focusing on stage I-III colon cancer revealed that comorbid diabetes is associated with elevated risk of postoperative complications in patients 80 and older after either open resection or laparoscopic resection in Finland [ 17 ].…”
Section: Introductionmentioning
confidence: 99%